Educational Proposal program and its effect on the learning and acquisition movements Free swimming for the disabled - S.Azieze, Mustapha; Sabih Ali, Ysar (Journal of Physical Education, 2012)
Has become a sport with disabilities to sports of great importance in the reconstruction and rehabilitation of people with special needs physically, "and emotionally" and physically "and mentally" It means effective and optimal speed the return of the disabled into society and softened with him again and his sense of being a member of the community members, which is an important part in its composition, the sport of swimming in the introduction to the sport, and therefore the researchers focus light on the category task in society and try to solve the research problem, which included the lack of the existence of special education programs especially athletes with special needs, through the achievement of goals, which included the preparation of an educational program rate proposal for the and know the effect of its use in education and the acquisition of free-swimming movements of persons with disabilities, Has been selected intentional for the research sample, which consisted of four athletes with disabilities within the category ninth subject of the study, which represented the community originally fully, and has been distributed to two equal groups, one trial used the proposed program and the other officer used the traditional program, and after the completion of the application of the educational program has been tested sample in freestyle, where it was concluded that the impact of the educational program proposed rate for positive "in the education and the acquisition of movements free-swimming for the disabled, and therefore recommended the researchers using the trainers and specialists tutorial proposed Amendment in the education and the acquisition of movements free-swimming for beginners with disabilities within the category ninth, as well as preparation of special education programs for other types of swimming (chest, back and butterfly) for athletes with disabilities into the ninth category, the researchers also recommended numbers of special education programs for beginners to swim within the categories of persons with disabilities other than physical disability.